Short Versions of Turkish Flow Scales for Athletes: Reliability and Validity Study - AŞÇI, FEVZİYE HÜLYA (SLOVAK ACAD SCIENCES INST EXPERIMENTAL PSYCHOLOGY, 2020)
The purpose of this study was to test the validity and reliability of the Short Flow State Scale-2 (SFSS-2) and Short Dispositional Flow Scale-2 (SDFS-2) for Turkish athletes in two separate studies. One hundred ninety-seven athletes (M-age = 22.05, SD = 3.60) voluntarily participated in the first study to test the psychometric properties of SDFS-2 and completed SDFS-2, Long Dispositional Flow Scale-2, and Sport Motivation Scale. In the second study, 423 athletes (M-age = 20.00, SD = 3.46) constituted the sample group and completed SFSS-2, Flow State Scale2, and Situational Motivation Scale for testing the psychometric properties of SFSS-2. Factor structures of both scales were examined by confirmatory factor analysis (CFA). Concurrent validity of the scales was examined by Pearson Product Moment Correlation analysis. The reliability evidence was obtained by a Cronbach's alpha values. The results of CFA from both studies revealed that both scales have nine items with one factor. All the correlation coefficients calculated for concurrent and convergent validity were significant (between 0.45-0.92 for SDFS-2 and 0.33-0.79 for SFSS-2). Cronbach's alpha coefficients calculated for internal consistency were 0.77 for SDFS-2 and 0.82 for SFSS-2. The results from both studies indicated that Turkish versions of SDFS-2 and SFSS-2 are valid and reliable instruments to be used in sports contexts.
Keywords: flow; construct validity; reliability; sport; DISPOSITIONAL FLOW; STATE SCALE-2; EXTRINSIC MOTIVATION; EXPERIENCE; STUDENTS; MINDFULNESS; TRANSLATION; VALIDATION; PSYCHOLOGY; CONSTRUCT